Collaborative Governance in Accelerating Regional Financial Access in South Sulawesi Province - Zaen, Fuad; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
Collaboration has emerged as a strategic approach in addressing the public issues by engaging multiple stakeholders, beyond relying solely on governmental institutions. The concept of collaborative governance—particularly through the Ansell and Gash model—offers a framework to assess how actors contribute to shared governance processes through their respective roles. This study examines the strategies and roles of key stakeholders within Tim Percepatan Akses Keuangan Daerah Provinsi Sulawesi Selatan (TPAKD) of South Sulawesi Province. It explores the potential application of collaborative governance in both the formulation and implementation of policies aimed at expanding regional financial access. The key actors analyzed include the Provincial Government of South Sulawesi, the Financial Services Authority (OJK) of South Sulawesi and West Sulawesi, Bank Indonesia’s South Sulawesi Representative Office, the Regional Office of the Directorate General of Treasury (Ministry of Finance), Lembaga Penjamin Simpanan (LPS) Region III – Sulawesi, Maluku, Papua, and the banking industry. This research adopts a qualitative methodology involving field observation, document analysis, and in-depth interviews with key stakeholders, aiming to uncover their respective roles and levels of participation within the TPAKD framework. The findings suggest that the collaborative model implemented by the TPAKD in South Sulawesi has been effectively operationalized. Each actor has contributed in alignment with their institutional mandates, thereby facilitating inclusive financial access for the people of South Sulawesi Province.